RELIGIOUS ORIENTATION, FAMILIAL TIES, AND RESPECT OF URBAN ELDERS: EVIDENCE FROM CROSS-SECTIONAL SURVEY IN IN LAHORE, PAKISTAN - YUMNA MEER, SADIA SAEED, RAHAT SHAH (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The present study was aimed to investigate the relationship between religious orientation, familial ties, and respect for elders. Respect for elders is decreasing even in traditional, developing, and patriarchal societies because of the interplay of globalized modern ideals and traditional values. Nevertheless, this is an important area of research because respect is closely correlated withthe social, physical, and psychological wellbeing of the elders. For achieving research objectives and testing hypotheses, the researcher conducted a cross-sectional survey. The survey was conducted among 400 elders who were selected using a probability sampling technique. Data were analyzed using SPSS IBM Version 21.0.Results of the study indicate a positive relationship between independent variables i.e. familial ties, religious orientation, and dependent variable respect of elders. An increase in respect for elders was noted among families that were more religious and integrated in comparison to less religious and less integrated families.